Vyuzití citacních rejstríků a impact factoru - Pitterová, K (Ceska a slovenska oftalmologie, 1999)
Article deals with evaluation method of scientific works by means of Citation Indexes and Impact Factor which are produced by Institute for Scientific Information of Philadelphia. It criticizes criteria of the usage of Impact factor and way of research workers evaluation.
Keywords: bibliometrie; publikování; výzkum; referování a indexace jako téma; Research; Bibliometrics; Publishing; Abstracting and Indexing